Making place in virus‐free space - Farbotko, Carol (Geographical Research, 2021)
As much a rapidly evolving cultural signifier as a viral materiality, COVID‐19 has not biologically penetrated every national border. It is, however, transforming the interpretation, understanding, and experience of place in the absence of infection. One role for geographers is to analyse how the material absence of COVID‐19 is manifesting spatially beyond closed borders. More specifically, how are particular places becoming meaningful as virus‐free? On that basis, this article offers a commentary and cultural geographic analysis of a road called COVID‐19 Road newly constructed on one of the islands of the Pacific nation, Tuvalu, and of migration during Tuvalu's pandemic state of emergency. The idea of rural security is central to national government advice for urbanites living on the main island of Funafuti to voluntarily return to one of the eight other rural islands to which they claim kinship ties. Those outer islands of Tuvalu, long mythologised as the nation's real heartland, are being constructed as secure, while the capital is insecure against COVID‐19 risk. Rural place is thus constituted as nurturing and safe, particularly because of a renewed policy focus on customary practices of food security. The amplification of such practices is intended to limit the need for reliance on cargo supplies and humanitarian aid from the infected outside world. Rurality, isolation, islandness, subsistence, and remoteness are pivotal to an emerging national narrative of Tuvalu as resourceful and resilient during the pandemic.